2018
DOI: 10.1016/j.addbeh.2017.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Opiate use disorders and overdose: Medical students' experiences, satisfaction with learning, and attitudes toward community naloxone provision

Abstract: Our findings suggest an unmet learning need in undergraduate training on opioid use disorder, with potential consequences for patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…14 The opioid overdose crisis has led some medical schools to create novel SUD curricula. 20,21 Although OUD training in medical school has been shown to improve students' knowledge, skills, and self-efficacy, [22][23][24][25] significant shortcomings remain 26 and there is limited guidance on best practices for implementing SUD education in medical curricula. 21 Furthermore, health professional education may play an important role in reducing inappropriate prescription of opioid medications for pain; increases in opioid prescribing have been associated with the development of OUDs so it is vital that future physicians be taught how to address pain appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…14 The opioid overdose crisis has led some medical schools to create novel SUD curricula. 20,21 Although OUD training in medical school has been shown to improve students' knowledge, skills, and self-efficacy, [22][23][24][25] significant shortcomings remain 26 and there is limited guidance on best practices for implementing SUD education in medical curricula. 21 Furthermore, health professional education may play an important role in reducing inappropriate prescription of opioid medications for pain; increases in opioid prescribing have been associated with the development of OUDs so it is vital that future physicians be taught how to address pain appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…Tobin et al found an unmet learning need in undergraduate training on opioid use disorder, 68 and Singh & Pushkin described how currently, medical education about the ethical dimensions of opioid prescribing lacks clarity, consistency and structure (p. 640). 69 …”
Section: Resultsmentioning
confidence: 99%
“…15 Currently, the United States of America suffers a crisis caused by a dramatic increase in the chronic use of opioid therapy, and its misuse and abuse has become a first-order problem. 67 Tobin et al found an unmet learning need in undergraduate training on opioid use disorder, 68 and Singh & Pushkin described how currently, medical education about the ethical dimensions of opioid prescribing lacks clarity, consistency and structure (p. 640). 69 Therefore, it is important to improve awareness and opioid-related education to address the knowledge gaps reported by students.…”
mentioning
confidence: 99%
“…Nevertheless, in a French survey, two of three GPs reported their refusal to see illicit drug users in consultation 6 . In Ireland, undergraduate students felt moderately prepared to recognize opioid use disorders 8 . In addition, pharmacy students' knowledge of injection drug patients was shown to be limited in the United States (US), while most of them received insufficient training to assist patients with SUDs 9,10 .…”
Section: Introductionmentioning
confidence: 99%